The Investigation of Some Phytochemical Compounds Found in Anchusa strigosa L. Grown Naturally in Iraq - Ghalib, Suroor A.; J. Kadhim, Enass (Iraqi Journal of Pharmaceutical Sciences, 2021)
Anchusa strigosa L.: Hardy annual biennial or perennial herb, with hairs especially on the leaves., flowers generally regular. Commonly named (Lisan Althour) in Iraq, from Boraginaceae family. The plant contains phenolic acids, flavonoids, alkaloids, sterols, and terpenoids. The Whole plant part defatted with n-hexane for 24 hours. The defatted plant material extracted using absolute methanol by Soxhlet apparatus for 24 hours, the extract fractionated by solvents of different polarity: petroleum ether- chloroform - ethylacetate- and n-butanol respectively. The n-butanol fraction hydrolyzed with 10% HCl for 5 hours by reflex to break down the glycosidic linkage. Rosmarinic acid, caffeic acid, genistein, and silybin were isolated from ethyl acetate fraction by preparative layer chromatography which identified by high performance liquid chromatography HPLC, Fourier transforms infrared (FTIR) spectra, thin- layer chromatography TLC and melting point. Since the plant contain alkaloids so acid- base extraction performed for crude extract resulting from the maceration of the plant parts in methanol (cold method) to obtain the alkaloid that isolated by preparative layer chromatography and then identified by Fourier transforms infrared (FTIR) spectra and thin-layer chromatography (TLC).The aim of this research was to carry out a phytochemical study of this plant since no previous phytochemical investigation work had been done on this species in Iraq.